Seismic performance of shell structure under earthquake loading - Rahamah Wati, Sulaeman (2017)
During past recent years, the number of building structural damage affected by earthquake is increase in Malaysia especially in Sabah. The reason of failure the structure because of inadequate design by Engineer without considering seismic effect in while designing the structure. Designing the structure must be considered several parameters such as the frequency of building can resists, the displacement and acceleration of the building . The mode shape should be study furthermore, which is the tendency of building will move during earthquake attack from the studies the engineer should be able to predict how to overcome when the problem occur. SAP2000 use to conducted the analysis , SAP2000 able to determine the best mode shape which is the best frequency and period of structure to built. The maximum acceleration and displacement are able to find out by using SAP2000. The best mode shape in this analysis are from mode shape 1 which is the frequency is 68.02 Hz and the period is 0.014701 sec . Maximum acceleration is 149442.9433 m/sec2 from axis Y and the value are get from the joint 128 . The highest displacement also occur from joint 128 at the Y axis where is the value are 0.299743 m. To design new spherical dome , we used 5% of damping which is the value maximum acceleration and displacement at the joint 128 used in the design later.